Wireless channel and noise characteristics in industrial internet of things - Ke ZHANG; Liu LIU; Ze YUAN; Kun ZHANG; Jianhua ZHANG; Zhijun LIU (Dianxin kexue)
With the proposal and implementation of “Made in China 2025” “IntelligentManufacturing” “Internet plus” and a series of national strategic planning,the industrial internet of things(IIoT)has developed rapidly in China.However,the channel and noise characteristics of the industrial poor environment have brought great challenges to the wireless communication of the industrial internet of things.The application of different wireless communication technologies in IIoT were introduced and compared and the features of wireless channel and noise in the environment of IIoT were summarized.As the key content of wireless communication research,channel and noise characteristics were analyzed overall.